2001
DOI: 10.1128/jvi.75.8.3960-3964.2001
|View full text |Cite
|
Sign up to set email alerts
|

Direct In Vitro Binding of Full-Length Human Immunodeficiency Virus Type 1 Nef Protein to CD4 Cytoplasmic Domain

Abstract: The Nef protein of the simian and human immunodeficiency viruses is known to directly bind and downregulate the CD4 receptor. Although the molecular mechanism is well understood, direct binding of Nef and CD4 is difficult to demonstrate and is believed to be of low affinity. Applying nuclear magnetic resonance and fluorescence spectroscopy, we biophysically reevaluated the CD4-Nef complex and found the dissociation constant to be in the submicromolar range. We conclude that additional, so far disregarded resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 42 publications
0
54
0
Order By: Relevance
“…Since internalization of raft-associated proteins may involve a clathrin-independent route, it may be that a key role of Nef is to target the clathrin-mediated endocytosis machinery to a location normally devoid of clathrin. Although nuclear magnetic resonance studies have shown that a full-length recombinant Nef protein interacts directly with a synthetic peptide derived from the cytoplasmic tail of CD4, Nef-CD4 binding has been difficult to demonstrate (53). It may be that a combination of CD4 binding and raft association by Nef is key to the forming of a stable Nef-CD4 complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since internalization of raft-associated proteins may involve a clathrin-independent route, it may be that a key role of Nef is to target the clathrin-mediated endocytosis machinery to a location normally devoid of clathrin. Although nuclear magnetic resonance studies have shown that a full-length recombinant Nef protein interacts directly with a synthetic peptide derived from the cytoplasmic tail of CD4, Nef-CD4 binding has been difficult to demonstrate (53). It may be that a combination of CD4 binding and raft association by Nef is key to the forming of a stable Nef-CD4 complex.…”
Section: Discussionmentioning
confidence: 99%
“…There is general agreement that Nef induces the internalization of CD4 via clathrin-coated pits, probably by binding directly to the cytoplasmic tail of CD4 (53), and then directly (14,49) or indirectly (26,40) linking to a cellular adaptor complex, most likely either AP-1 (7,17) or AP-2 (17,26,30). Nef has also been implicated in a second step that targets CD4 to lysosomes for degradation (33,50).…”
mentioning
confidence: 99%
“…Instead, Nef accelerates the endocytosis of CD4 and targets the internalized molecules to the lumen of lysosomes for degradation (Aiken et al, 1994;Rhee and Marsh, 1994). To accomplish this, Nef directly binds the cytosolic tail of CD4 (Grzesiek et al, 1996;Preusser et al, 2001;Rossi et al, 1996) and the endocytic adaptor protein 2 (AP-2) (Chaudhuri et al, 2007(Chaudhuri et al, , 2009Doray et al, 2007;Lindwasser et al, 2008). This activity promotes the cooperative assembly of a tripartite Nef-AP-2-CD4 complex (Chaudhuri et al, 2009;Ren et al, 2014) that induces the endocytosis of CD4 mediated by clathrin-coated vesicles (CCVs) (Burtey et al, 2007;Greenberg et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Replacing the CD4 tail with Nef results in a chimeric protein that down-regulates CD4 in trans as well as the chimeric protein itself in cis (23). Several studies have shown that CD4 interacts directly with Nef in vitro and in insect cells and that the dileucine motif in the CD4 tail is essential for the interaction (25,26,28,29). However, the direct interaction between CD4 and Nef in mammalian cells has yet to be demonstrated (24).…”
mentioning
confidence: 99%